2022
DOI: 10.3390/ma15093198
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Scanning Strategies and Laser Remelting Effects on Top Surface Deformation of Additively Manufactured IN 625

Abstract: The main drawbacks of the Laser Powder Bed Fusion (LPBF) process are the surface quality and dimensional accuracy of manufactured parts due to the edge and corner effects. These effects can be diminished by using an appropriate balance of the process parameters and scanning strategies. This paper focuses on the assessment of reducing the edge and corner effects that occur in additively manufactured IN 625 alloy via the LPBF technique by varying the hatch angle rotation (by 45°, 67°, and 90°) and volumetric ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…During rapid solidification, the elevated ridges become more prominent, especially in the cases of samples built with the 67 • and chessboard scanning strategies. This adverse effect is primarily attributed to compressive stress around the corners and the thermal warping effect [37,38], which can lead to significant distortions in additively manufactured components [36]. As seen in Figures 6-9, the distortions of bridge pieces become more pronounced after the removal from the base plate (after cut).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During rapid solidification, the elevated ridges become more prominent, especially in the cases of samples built with the 67 • and chessboard scanning strategies. This adverse effect is primarily attributed to compressive stress around the corners and the thermal warping effect [37,38], which can lead to significant distortions in additively manufactured components [36]. As seen in Figures 6-9, the distortions of bridge pieces become more pronounced after the removal from the base plate (after cut).…”
Section: Resultsmentioning
confidence: 99%
“…These factors are directly influenced by the pattern, where the scan could be an entire layer, separated islands, or a stripe in the chessboard. Although 90 • , 45 • , and 67 • are commonly used hatch angles for bi-directional scanning, a previous study on top surface deformation of AMed IN 625 demonstrated that the differences in terms of edge width and height between 90 • and 67 • angles are relatively close, while the hatch angle of 45 • induces the highest deformations [36].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations